Cactus-like iron diphosphide@carbon nanotubes composites as advanced anode materials for lithium-ion batteries. (1st January 2018) - Chen, Xibang; Qiu, Jingyi; Wang, Yimeng; Huang, Furong; Peng, Jing; Li, Jiuqiang; Zhai, Maolin
Abstract: The ball-cactus-like iron diphosphide@carbon nanotubes (FeP2 @CNTs) composites are synthesized via a simple chemical vapor deposition (CVD) with two-step heating method. SEM, TEM, XRD and Raman spectrum confirm that FeP2 and CNTs exist as the core and the surrounding spines of the ball-cactus-like composite, respectively, for FeP2 @CNTs synthesized under suitable conditions. With optimized FeP2 @CNTs composite containing ball-catus-like structure as the anode of LIBs, the assembled batteries exhibit an initial coulombic efficiency of 91.6%. Furthermore, this kind of battery delivers a stable and high discharge specific capacity of 736.2 mAh g −1 at 0.1 C (1 C = 1365 mA g −1 ) after 100 cycles. Even at a higher rate of 2.5 C, it still delivers a stable discharge specific capacity of 650.2 mAh g −1 within 100 cycles with negligible capacity fading, much higher than the reported results to date. This excellent electrochemical performance of FeP2 @CNTs composite is attributed to the cladding of FeP2 with CNTs, which prevent the large volume changes of FeP2 and improve the electrical conductivity of composites.